Potential Role of Superoxide Dismutase 3 (SOD3) in Resistance to Influenza A Virus Infection - Feimin Chen; Liurong Chen; Jinlong Liang; Zhixuan Chen; Chunyu Zhang; Zhengyin Zhang; Jie Yang (MDPI AG, 2023)
Influenza A virus infection induces the production of excessive reactive oxygen species (ROS). Overproduction of ROS can overwhelm the antioxidant defense system, leading to increasing intensive oxidative stress. However, antioxidant defense against oxidative damage induced by influenza A virus infection, and in particular the significance of the SOD3 response in the pathogenesis of influenza virus infection, has not been well characterized. Here, we investigated the potential role of SOD3 in resistance to influenza A virus infection. In this study, SOD3, as an important antioxidant enzyme, was shown to be highly elevated in A549 cells following influenza A virus infection. Furthermore, inhibition of SOD3 impacted viral replication and virulence. We found that SOD3 disrupts IAV replication by impairing the synthesis of vRNA, whereas it did not affect viral ribonucleoprotein nuclear export. In addition, overexpression of SOD3 greatly reduced the levels of ROS caused by influenza A virus infection, regulated the inflammatory response to virus infection by inhibiting the phosphorylation of p65 of the NF-κB signaling pathway, and inhibited virus-induced apoptosis to a certain extent. Taken together, these findings indicate that SOD3 is actively involved in influenza A virus replication. Pharmacological modulation or targeting of SOD3 may pave the way for a novel therapeutic approach to combating influenza A virus infection.